2015
DOI: 10.1103/physrevb.91.201103
|View full text |Cite
|
Sign up to set email alerts
|

Random phase approximation up to the melting point: Impact of anharmonicity and nonlocal many-body effects on the thermodynamics of Au

Abstract: Application of the generalized gradient corrected functional within standard density-functional theory results in a dramatic failure for Au, leading to divergent thermodynamic properties well below the melting point. By combining the upsampled thermodynamic integration using Langevin dynamics technique with the random phase approximation, we show that inclusion of nonlocal many-body effects leads to a stabilization and to an excellent agreement with experiment. Most present-day ab initio databases contain resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The same behavior has been reported previously for Au [35], where the heat capacity calculated within the quasiharmonic approximation diverged in a similar manner for the GGA results. In that work it was found that the inclusion of anharmonic contributions only partially corrected this unphysical divergence, which could be fully removed by including a treatment of exchange and correlation within the random phase approximation (RPA).…”
Section: B Resultssupporting
confidence: 88%
“…The same behavior has been reported previously for Au [35], where the heat capacity calculated within the quasiharmonic approximation diverged in a similar manner for the GGA results. In that work it was found that the inclusion of anharmonic contributions only partially corrected this unphysical divergence, which could be fully removed by including a treatment of exchange and correlation within the random phase approximation (RPA).…”
Section: B Resultssupporting
confidence: 88%
“…There are a number of approaches in the literature to calculate the anharmonic vibrational properties of crystals, [1][2][3][4][12][13][14][15][16][17][18][19][20][21][22] including thermodynamic integration 23 (TI), which is the method used in this work. In TI the anharmonic part of the full Hamiltonian, E − E qh , is switched on with the parameter λ ∈ [0, 1], in this instance linearly as E mix (λ) = E qh + λ(E − E qh ).…”
Section: A Backgroundmentioning
confidence: 99%
“…As discussed above, the inclusion of magnetic excitations and their impact on vibrational properties for magnetic materials such as CrN is crucial. Advancements beyond the above described approximations are being developed, for example, to treat defected and/or disordered systems (e.g., to account at elevated temperatures for thermodynamically driven creation of vacancies [126,144,157] or temperature-driven partitioning of substitutionally alloyed steels [158] ), the delicate interplay between various magnetic excitations (e.g., longitudinal spin fluctuations) and lattice vibrations (e.g., explicit anharmonic contributions) [135,136] or for predictions in multi-component systems, such as the new class of high entropy alloys. [45] Taking the magnetic contributions properly into account, the standard GGA approximation yielded T N ¼ 428K.…”
Section: Ab Initio Thermodynamicsmentioning
confidence: 99%
“…[38] These results demonstrate the predictive power of current theoretical approaches, which can be applied to many systems of practical interest, in particular in light of the nowadays available and ongoing increasing computational power. Advancements beyond the above described approximations are being developed, for example, to treat defected and/or disordered systems (e.g., to account at elevated temperatures for thermodynamically driven creation of vacancies [126,144,157] or temperature-driven partitioning of substitutionally alloyed steels [158] ), the delicate interplay between various magnetic excitations (e.g., longitudinal spin fluctuations) and lattice vibrations (e.g., explicit anharmonic contributions) [135,136] or for predictions in multi-component systems, such as the new class of high entropy alloys. [140,141,159,160] An important application field for "ab initio" thermodynamic data is using them as input for the CALPHAD method [161][162][163][164][165][166] implemented in simulation packages, such as Thermocalc [167] and Matcalc.…”
Section: Ab Initio Thermodynamicsmentioning
confidence: 99%